Pengujian Sifat Anti-Inflamasi Ekstrak Bunga Chamomile dalam Nanopartikel Kristal Cair Lyotropik Secara In Vitro - Widyan Muchzadi Akbar; Muhammad Dzakwan; Fransiska Leviana (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Chamomile is renowned for its anti-inflammatory properties. Lyotropic Liquid Crystal Nanoparticle (LLCN) offers better enhancement of the bioavailability and efficacy of natural products. This study evaluated the LLCN system’s effectiveness in improving chamomile extract’s anti-inflammatory activity and compliance with nanoparticle standards. Chamomile 70% ethanol extract was prepared, and the total phenolic and flavonoid content was measured. The extract was formulated into LLCN, and the particle size, polydispersity index, zeta potential, stability, and entrapment efficiency were evaluated. Anti-inflammatory activity was tested in vitro using the protein denaturation inhibition method. The extract showed high phenolic and flavonoid content. The characterisation results demonstrated that the LLCN system met the required specifications, exhibiting particle size values of 230.366±3.412 nm, polydispersity index of 0.217±0.034, a zeta potential of -23.763±0.756 mV, and an entrapment efficiency of 84.060%±0.100. Stability testing indicated that storage at 4°C was more effective than room temperature, preserving a smaller particle size and improving overall stability. The LLCN system significantly enhanced the extract’s anti-inflammatory activity, as demonstrated by a lower IC50 value than the viscous extract. In conclusion, the LLCN system enhances the therapeutic potential of chamomile extract and represents a promising strategy for developing phytochemical-based anti-inflammatory formulations.